2012
DOI: 10.1590/s0100-06832012000500004
|View full text |Cite
|
Sign up to set email alerts
|

Soil fauna as an indicator of soil quality in forest stands, pasture and secondary forest

Abstract: SUMMARYThe interactions between soil invertebrates and environmental variations are relatively unknown in the assessment of soil quality. The objective of this study was to evaluate soil quality in areas with different soil management systems, based on soil fauna as indicator, in Além Paraíba, Minas Gerais, Brazil. The soil invertebrate community was sampled using pitfall traps, in the dry and rainy seasons, from areas with five vegetation types (acacia, mimosa, eucalyptus, pasture, and secondary forest). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 19 publications
1
15
0
3
Order By: Relevance
“…Several factors may influence the soil invertebrate community, particularly season, microclimate, soil, and crop management, and resource availability [16, 17, 21]. With regard to the season, indeed rainfall might contribute to a more favorable environment for fauna activity at the semiarid region of northeast Brazil.…”
Section: Resultsmentioning
confidence: 99%
“…Several factors may influence the soil invertebrate community, particularly season, microclimate, soil, and crop management, and resource availability [16, 17, 21]. With regard to the season, indeed rainfall might contribute to a more favorable environment for fauna activity at the semiarid region of northeast Brazil.…”
Section: Resultsmentioning
confidence: 99%
“…In this sense, the greater and lesser density of edaphic fauna found in April/2013 and January/2014 (Table 3), respectively, is justified in part. A number of researchers have reported on the relationship of SM to the diversity and density of the fauna (CUNHA-NETO et al 2012;ABREU et al 2014;GARLET et al 2015). Machado et al (2015) reported the highest number of organisms during periods of higher rainfall, but when they investigated the edaphic fauna in a fragment of the Semideciduous Seasonal Forest in Rio de Janeiro, they found fewer faunal representatives in the dry season, as it also was found in this inquire.…”
Section: Accessory Variablesmentioning
confidence: 57%
“…The presence of one or more groups may be indicative of the quality of a specific environment even if the frequency of their occurrence is low (Cunha-Neto et al, 2012;Machado et al, 2015). The group classified as "Others" had low ratios in all areas evaluated, with percentages below 7%, as observed in the forest area in the dry season (Figure 2).…”
Section: Epigeal Faunamentioning
confidence: 97%